Editorial - Volume 4, Issue 1 - Kristy L Archuleta (Journal of Financial Therapy, 2013)
The theme for this issue’s editorial is “change.” Sometimes change can be difficult, however the change experienced by the Journal thus far this year is exciting!
Keywords: financial therapy